2013
DOI: 10.1016/j.jsp.2013.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of retention in elementary grades on transition to middle school

Abstract: The authors investigated the effects of retention in grades 1 to 5 on students’ reading and math achievement, teacher-rated engagement, and student-reported school belonging in middle school. From a multiethnic sample (N = 784) of children who scored below the median on a test of literacy in grade 1, an average of 75 students subsequently retained in grades 1 to 5 were matched with an average of 299 continuously promoted students on the basis of propensity to be retained in the elementary grades. A total of 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 63 publications
1
29
2
2
Order By: Relevance
“…Furthermore, retention in first grade did not appear to harm students’ psychosocial adjustment at grade 4 and bestowed benefits in terms of engagement in the classroom, sense of school belonging, and perceived academic self-efficacy (Wu, West, & Hughes, 2010, 2010). At the transition to middle school, students retained in the elementary grades (grades 1–5) did not differ from matched, continuously promoted children on level of academic achievement or sense of school belonging, nor did they differ in rate of change on these variables across the middle school grades (Im, Hughes, Kwok, Puckett, & Cerda, 2013). Finally, at the transition to high school, students retained in grades 1–5 and matched, continuously promoted students did not differ in their self-reported motivation to complete high school or to enroll in post-secondary education (Cham et al, 2015).…”
Section: Results Of Prior Studies With Current Longitudinal Samplementioning
confidence: 82%
“…Furthermore, retention in first grade did not appear to harm students’ psychosocial adjustment at grade 4 and bestowed benefits in terms of engagement in the classroom, sense of school belonging, and perceived academic self-efficacy (Wu, West, & Hughes, 2010, 2010). At the transition to middle school, students retained in the elementary grades (grades 1–5) did not differ from matched, continuously promoted children on level of academic achievement or sense of school belonging, nor did they differ in rate of change on these variables across the middle school grades (Im, Hughes, Kwok, Puckett, & Cerda, 2013). Finally, at the transition to high school, students retained in grades 1–5 and matched, continuously promoted students did not differ in their self-reported motivation to complete high school or to enroll in post-secondary education (Cham et al, 2015).…”
Section: Results Of Prior Studies With Current Longitudinal Samplementioning
confidence: 82%
“…A total of 67 covariates (potential confounders), all of which were measured in grade 1 before retention occurred, were used to estimate the propensity scores of the retained and promoted students (Im et al, 2013). These 67 covariates were selected to be as comprehensive as possible, including variables that have been shown in prior research to be associated with grade retention or academic achievement.…”
Section: Methodsmentioning
confidence: 99%
“…Using the same longitudinal sample as the current study, Im, Hughes, Kwok, Puckett, and Cerda (2013) investigated the effect of retention in grades 1–5 on students’ psychosocial and academic adjustment in middle school. Using propensity score matching to equate the retained and promoted students, piecewise growth curve modeling showed that students retained in the elementary grades and their promoted peers did not differ on measures of teacher-rated engagement, student reported school belonging, or academic achievement in the last year of elementary school, nor did they differ in their post-transition growth trajectories on these variables.…”
Section: Grade Retention As Risk Factor For Dropping Out Of Schoolmentioning
confidence: 99%
“…The negative effect of grade retention was further emphasized by Myung et al (2013) in a study conducted in the USA. The study investigated the effect of retention in grades 1 to 5 on reading and mathematics.…”
Section: Ap and Student Dropoutmentioning
confidence: 99%
“…In particular, grade retention is associated with increased expenditure for both governments and households, stigmatization of the affected students, low self-esteem, which more often than not lead to dropout (Myung et al, 2013;Manacorda, 2006;Glick & Sahn, 2010). Given the overwhelming empirical evidence linking grade retention to student dropout, the opponents of grade retention have argued for it to be mitigated or eradicated.…”
mentioning
confidence: 99%